Effect of impurities and sintering temperature on properties of MgO-CaZrO3 ceramic - Booth, Raul Fernando Nicolas (2013)
CaZrO3 -MgO ceramics are useful as refractories in kilns for the cement production. One method of manufacture of such ceramics is by sintering from m-ZrO2 and dolomite MgCa(CO3 )2 mixtures. In this work electrofused m-ZrO2 grains (fraction <M325) and two Argentinean dolomites with different mineralogical compositions were used as raw materials. Ceramics were obtained by the conventional powder method of uniaxial pressing and subsequent sintering at 1400 to 1680 °C. The influence of the different mineralogy of the dolomites and sintering temperature on the properties of the composites was investigated. Ceramics had 20-30% porosity with representative SEM-EDX microstructure constituted by CaZrO3 agglomerates of variable size (~100µm) and MgO grains (size <50µm) containing some unreacted m-ZrO2 grains. The elastic modulus and flexural strength were correlated with the presence of impurities of the dolomite, porosity and microstructure of the ceramic.